Dialogue among civilizations - Castro, Fidel, 1926-2016 (Oficina de Publicaciones del Consejo de Estado, 2007)
Speech given by Commander in Chief at the United Nations Conference on Environment and Development, in Rio De Janeiro, on June 12, 1992 and at the closing session of "Dialogue among Civilizations World Conference. Latin America in the 21st Century: Universalism and Originality," in Havana’s International Convention Center, on March 30, 2005.